Predictors and Clinical Importance of Postoperative Coronal Malalignment After Surgery to Correct Adult Spinal Deformity. Issue 7 (August 2020) - Tanaka, Nobuki; Ebata, Shigeto; Oda, Kotaro; Oba, Hiroki; Haro, Hirotaka; Ohba, Tetsuro
Abstract : Study Design: A retrospective observational study of a cohort of consecutive patients. Objective: The objective of this study was to determine the correlations between clinical outcomes of spinal surgery to correct adult spinal deformity (ASD) including mechanical complications and coronal malalignment and clarify the risk factors for postoperative coronal malalignment. Summary of Background Data: Despite the coronal malalignment seen regularly in adult patients who have undergone spinal surgery to correct spinal deformity, the associations between coronal malalignment, and clinical outcomes including mechanical complications after the surgery have remained unclear until now. To understand the associations between coronal malalignment and outcomes of surgery to correct ASD, and risk factors for postoperative coronal malalignment has substantial clinical importance. Materials and Methods: We included data from 121 consecutive patients who had undergone spinal surgery to correct ASD and were followed up for a minimum of 2 years. Iliac screws were used for pelvic fixation in all cases. The coronal balance was defined as the horizontal distance between the midpoint of C7 and the center of the sacrum on the coronal plane, and coronal malalignment was defined as when the absolute coronal balance was >20 mm. Preoperative radiographic parameters, surgical features, and clinical outcomes including mechanical complications were compared between groups of patients with coronal balance and those with malalignment. Univariate and multivariate regression analysis were used to clarify risk factors for postoperative coronal malalignment. Results: Postoperative coronal malalignment had no significant association with the clinical outcome as evaluated by a Roland-Morris Disability Questionnaire and Oswestry Disability Index but had a significant association with the frequency of rod fracture. A large preoperative coronal imbalance (malalignment), L5 coronal tilt angle, and use of lateral lumbar interbody fusion were found as risk factors for postoperative coronal malalignment. Conclusion: Postoperative coronal malalignment had no significant association with the clinical outcome as evaluated by the Oswestry Disability Index and Roland-Morris Disability Questionnaire but was significantly associated with the frequency of rod fracture. Level of Evidence: Level III.